(untitled) (Our Nature, 2015)
The publisher doubts that Russel´s Viper (Daboia russelii) to occur in Sarlahi, the central lowlands of Nepal because the last photo voucher in page 205 was not supportive to claim D. russelii. Rather, the specimen is Ovophis monticola. DOI: http://dx.doi.org/10.3126/on.v12i1.12259 Our Nature (2014), 12(1): 60-61.